2017
DOI: 10.1038/s41598-017-16144-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential prognostic value of MYC immunohistochemistry in subtypes of papillary renal cell carcinoma

Abstract: The histomorphological subtyping of papillary renal cell carcinomas (pRCCs) has improved the predictions of patients’ long-term survival. Based on our previous results, we hypothesized that the MYC proto-oncogene would show differential expression in pRCC subtypes. Using a multi-institutional cohort of 204 pRCC patients we assessed the additional value of the immunohistochemical markers MYC, MINA53, and Ki67 in predicting patient’s long-term survival. The clinical endpoints were overall survival (OS) and cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
2
7
1
Order By: Relevance
“…The relative downregulation of let-7c in type 2 pRCC corroborates the recent discovery of MYC overexpression in the respective subtype [61,68]. In addition, immunohistochemical MYC straining patterns could discriminate prognostic groups in type 1 pRCC [69].…”
Section: Discussionsupporting
confidence: 80%
“…The relative downregulation of let-7c in type 2 pRCC corroborates the recent discovery of MYC overexpression in the respective subtype [61,68]. In addition, immunohistochemical MYC straining patterns could discriminate prognostic groups in type 1 pRCC [69].…”
Section: Discussionsupporting
confidence: 80%
“…Some previous studies have demonstrated that type 2 pRCC was associated with worse survival than type 1 (3,13,25,29). However, the conclusion must be taken with caution, as these studies may be limited by sample size, short duration of follow-up, or the infrequency of death related to pRCC (25,26). And some recent studies hold the view that histological subtype is not an independent prognostic marker (9).…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of included studies are presented in Table 1 (3,(6)(7)(8)(9)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). All included studies were in retrospective designs and were published between 2001 and 2020, and the patients were recruited ranged from 1970 to 2018.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Specimens were obtained from the PANZAR consortium-a collaboration between the following institutions (in alphabetical order): Erlangen, Heidelberg, Herne, Homburg, Mainz, Mannheim, Marburg, Muenster, LMU Munich, TU Munich, and Regensburg [26][27][28][29]. The cohort consists of 368 patients.…”
Section: Patient Cohort and Tumor Characteristicsmentioning
confidence: 99%